Delving into Inquiry Learning in Teacher Education at the University of British Columbia - Rushton, Claire; Webb, Andrea (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
This paper discusses a series of inquiry-based seminars that are central to the teacher education program at the University of British Columbia. This teacher education program reflects the changing curriculum in the province. The new inquiry-based provincial curriculum is being implemented between 2015 and 2018 and the teacher education program is changing to reflect the practical needs of the teacher candidates. As teacher candidates become more familiar with the practices of inquiry, their professional practice changes as well.